Integrating GPR and RIP Methods for Water Surface Detection of Geological Structures - Chieh-Hou Yang; Lun-Tao Tong; Chun-Yi Yu (Terrestrial, Atmospheric and Oceanic Sciences, 2006)

(untitled)
Geophysical surveying in water-covered and swampy areas is particularly challenging. This paper presents a new survey strategy for such surveying that integrates ground penetrating radar (GPR) and resistivity image profiling (RIP) methods at the water surface to investigate geologic structures beneath rivers, ponds, and swamps.